From oil spills to barley growth – oil‐degrading soil bacteria and their promoting effects. (14th September 2016) - Mikolasch, Annett; Reinhard, Anne; Alimbetova, Anna; Omirbekova, Anel; Pasler, Lisa; Schumann, Peter; Kabisch, Johannes; Mukasheva, Togzhan; Schauer, Frieder
Abstract : Heavy contamination of soils by crude oil is omnipresent in areas of oil recovery and exploitation. Bioremediation by indigenous plants in cooperation with hydrocarbon degrading microorganisms is an economically and ecologically feasible means to reclaim contaminated soils. To study the effects of indigenous soil bacteria capable of utilizing oil hydrocarbons on biomass production of plants growing in oil‐contaminated soils eight bacterial strains were isolated from contaminated soils in Kazakhstan and characterized for their abilities to degrade oil components. Four of them, identified as species of Gordonia and Rhodococcus turned out to be effective degraders. They produced a variety of organic acids from oil components, of which 59 were identified and 7 of them are hitherto unknown acidic oil metabolites. One of them, Rhodococcus erythropolis SBUG 2054, utilized more than 140 oil components. Inoculating barley seeds together with different combinations of these bacterial strains restored normal growth of the plants on contaminated soils, demonstrating the power of this approach for bioremediation. Furthermore, we suggest that the plant promoting effect of these bacteria is not only due to the elimination of toxic oil hydrocarbons but possibly also to the accumulation of a variety of organic acids which modulate the barley's rhizosphere environment.